Keragaan Hasil Varietas Unggul Baru (Vub) Padi Sawah Lahan Sawah Tadah Hujan pada Dua Musim Tanam yang Berbeda di Kabupaten Seluma Provinsi Bengkulu - Yartiwi Yartiwi; Ahmad Damiri; Irma Calista Siagian; Heryan Iswadi (Seminar Nasional Lahan Suboptimal, 2018)
Yartiwi et al, 2019.The Diversity of New Superior Variety (Vub) of Rice at Rainfed Land in Two Different Seasons in Seluma District, Bengkulu Province. pp. 216-224.The planting season is one of the factors influencing the yield in the cultivation of rice plant, the use of new adaptive superior varieties is one of the technologies to increase the productivity of paddy rice. The purpose of the study was to see the growth viability and the results of several new improved varieties of paddy fields on rainfed land planted in two different planting seasons in Seluma Regency, Bengkulu Province. This study was conducted in Karang Dapo Village, Semidang Alas Maras District, Seluma Regency, from April to December 2017. The assessment was carried out using a Randomized Block Design (RBD) with 2 factors. The first factor is the treatment of variety (V) which consists of 4 levels of treatment. The second factor is the planting season (MT), which consists of 2 levels, resulting in 8 treatment combinations. Each treatment combination was repeated 3 times. Number of plants sample 10 plants / replications. Analysis carried out on quantitative data observations from vegetative and generative growth component variables using the F test at the level of 5%. If there are significant differences between treatments, further testing is carried out with the LSD test at 5% level. The results of the research showed that in the rainy season the production was higher compared to the results in the dry season, seen from the performance of growth and yield obtained by Inpari 39, 41 and Situbagendit varieties which were more adaptive compared to existing varieties.